Integrative transcriptomic and proteomic analyses reveal a positive role of BES1 in salt tolerance in Arabidopsis - Feng, Lei; Li, Yan; Zhou, Yu-Ling; Meng, Guang-Hua; Ji, Zhao-Lin; Lin, Wen-Hui; He, Jun-Xian (Frontiers in Plant Science, 2023)
Salt stress is a major environmental factor limiting plant growth and development. Previous studies have indicated that the steroidal hormones—brassinosteroids (BRs) are important regulators of plant responses to salt stress. However, the underlying molecular mechanisms have not been fully understood. Here, we report that bes1-D, a gain-of-function mutant of the BR-regulated transcriptional factor BES1 in Arabidopsis showed better salt tolerance than the wild-type plant, while a BES1 RNA interference (BES1-RNAi) line was more sensitive to salt stress. Global gene expression profiling and time series clustering analyses identified a total of 1,170 genes whose expression was boosted in bes1-D under salt stress. Further GO enrichment and gene functional network analyses identified several key modules that are regulated by BES1 and most sensitive to salt stress perturbations, including stress response, response to ABA and ROS, flavonoid biosynthesis and transmembrane transport. A comparative proteomic analysis performed under the same stress conditions supported the results from the transcriptome analysis. In addition, transient gene transcription assays in Arabidopsis protoplasts and in vitro DNA binding assay verified that BES1 directly regulates the expression of two ion transporter genes NHX2 and CAX3. Taken together, our results support a positive role of BES1 in plant salt tolerance.